Membentuk Karakter Anti Korupsi pada Generasi Muda dengan Nilai-Nilai Luhur Pancasila - Moh. Ali Hofi (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
The easy generation as the successor to the future generation of the nation has an important and urgent role on its shoulders. One of the roles that must be shared by the nation's generation, especially millennials, is how they are able and have a character that is in accordance with the noble values ​​of Pancasila, especially in law enforcement and anti-corruption behavior. It is important to know that corruption is a problem in Indonesia that has not yet been resolved and there tends to be an increase in cases from the previous year. This indicates that the regeneration of the Indonesian nation is on the verge of failure in forming the character of an anti-corruption generation of the nation. By actively and massively applying and implementing Pancasila values, it is hoped that this anti-corruption attitude will be able to grow. In this article, the normative research type is used to analyze the above issues which are the focus of the research. The results of the research show that the existence of Pancasila as a way of life for the younger generation of the Indonesian nation is not working effectively, so concrete efforts are needed to instill these values, one of which is education and the formation of the Pancasila character, both through formal/educational and non-formal institutions.